PASTRAB: a model for simulating intake regulation and growth of rabbits raised on pastures. (4th December 2017) - Joly, L.; Goby, J.-P.; Duprat, A.; Legendre, H.; Savietto, D.; Gidenne, T.; Martin, G.
Abstract : Given the very recent investment in research on organic rabbit production, many knowledge gaps remain. Simulation models based on data from experiments and farms may help generate general principles for organic rabbit production. Our goals were to (i) develop a model to simulate intake regulation and growth of rabbits raised on pastures, (ii) validate this model under a diversity of conditions and (iii) conduct a simulation experiment to predict the potential to decrease the supply of complete feed by increasing the grazing area per rabbit. The model developed (PASTRAB) simulates organic rabbit fattening on pastures in four main submodels that represent dynamics of (i) herbage standing biomass, fill and feed values; (ii) intake of herbage, complementary feed (i.e. complete pellets, cereal–legume grain mixtures) and hay as regulated by herbage allowance, fill and feed values of feedstuffs and rabbit physiological parameters; (iii) conversion of rabbit intake into live weight gain; and (iv) rabbit mortality. The model also calculates gross margin per rabbit sold. Model accuracy was assessed by considering the fit between observed and predicted herbage intake, which was low, with a relative root mean square error (rRMSE) of 51% and 66% on grass-based and legume-based pastures, respectively. However, the standard deviations of observed herbage intake were similar to the root mean square error of predicted herbage intake, indicating that it would have been difficult to improve model calibration. The fit between observed and predicted rabbit live weight was acceptable, with an rRMSE of 11% and 10% for grass-based and legume-based pastures, respectively. Simulated scenarios showed that a decrease in complementary feed combined with an increase in the grazing area per rabbit had little impact on average daily growth and gross margin per rabbit but increased herbage use efficiency. With 90 g of complementary feed per day and grazing of 0.4 m²/rabbit per day, herbage use efficiency was 22%, with average daily growth of 21.6 g/day and gross margin of 18.80 €/rabbit. With no complementary feed and grazing of 1.2 m²/rabbit per day, average daily growth decreased (19.2 g/day), but herbage use efficiency reached 100% and gross margin reached 19.20 €/rabbit. We used PASTRAB in participatory workshops with farmers so that the latter could explore adaptations to their current practices. Overall, farmers considered the model predictions realistic, and some of them decided to adapt some of their management practices immediately after the workshops.